Pengaruh Literasi Keuangan, Financial Technology, dan Lingkungan Sosial Terhadap Perilaku Keuangan Mahasiswa di Kota Batam - Dewi Febrianti; Argo Putra Prima (eCo-Buss, 2024)
Financial behavior is a person's pattern of behavior in managing finances to meet needs or prepare for the future. This is very important to know so that you can properly manage your financial patterns so as not to induce consumer-oriented financial behavior. Students are expected to be able to manage their money in the digital age, as they are millennials and need to be prepared for ever-accelerating technological developments.This research investigates whether students understand financial behavior, tests and analyzes the influence of financial literacy, financial technology, and  social environment on financial behavior, and tests and analyzes the correlation between financial behavior and each variable. It was carried out for the purpose of analysis. The population and sample of this study are current accounting students in several universities in Batam city, such as Universitas Batam, Universitas Internasional Batam, Universitas Riau Kepualauan, and others. The number of respondents for this survey was 300. Purposive sampling technique and Likert scale were used for the sample. Data were processed using the statistical program SPSS v29. This research chose to use quantitative research methods. The research results show that financial literacy and financial technology partially have a significant and positive influence on financial behavior, but do not have a significant influence on the social environment on financial behavior. However, the results of another test, namely the F test, indicate that financial literacy, financial technology